Dynamic mechanical and creep properties of poly(ether ketone)-graphite nanoplatelet (GNP) nanocomposites. Issue 15 (13th October 2019) - Gaikwad, S. D.; Dravid, S. V.; Sonawane, B.U.; Abraham, Mathew; Goyal, R. K.
ABSTRACT: Poly(ether ketone) (PEK) matrix nanocomposites containing graphite nanoplatelet (GNP) were prepared through planetary ball mill followed by hot pressing for the creep and creep recovery study. The creep behavior was studied in the linear viscoelastic region at three different temperatures (75–125℃). The incorporation of 0.5 wt.% GNP has significantly increased the creep resistance. However, further addition of GNP into the matrix lowered the rate of increase in creep resistance. All nanocomposites showed an increase in glass transition temperature, dimensional stability, and storage modulus compared to pure PEK. Findley power law fits nicely the creep data. GRAPHICAL ABSTRACT: